2023
DOI: 10.1111/jan.15753
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership behaviour of head nurse assessment and its linkage with nurse work engagement in China

Abstract: AimTo assess the servant leadership behaviour of head nurse and its linkage with nurse work engagement in China.DesignA cross‐sectional study.MethodsA anonymous investigation with the stratified cluster randomized sampling of nurse was conducted in Hunan Province of China in December 2020. We administered the Perceived Head Nurse Service Leadership Behaviour Scale and the Chinese version of Utrecht work engagement scale to survey, and analyse its relationships by multiple linear regression.ResultsA number of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
6
0
Order By: Relevance
“… Compared to transformational leadership, transactional leadership strongly impacts employee engagement.58 Asiri, Mahran, Elseesy 57 Al-Dossary 58 Servant leadership There is a strong positive effect of servant leadership on work engagement. Qin, Li, Li 59 Ethical leadership Positive relationship with work engagement. Ethical leadership is mediated and moderated by work meaningfulness associated with work engagement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Compared to transformational leadership, transactional leadership strongly impacts employee engagement.58 Asiri, Mahran, Elseesy 57 Al-Dossary 58 Servant leadership There is a strong positive effect of servant leadership on work engagement. Qin, Li, Li 59 Ethical leadership Positive relationship with work engagement. Ethical leadership is mediated and moderated by work meaningfulness associated with work engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Leadership is the dynamic process of guiding individuals or groups toward shared goals. Findings from six studies reveal diverse leadership styles influencing work engagement, including Transformational leadership, 21 , 57 , 58 Transactional leadership, 57 , 58 Servant leadership, 59 Ethical leadership, 50 Humble leadership, 60 and Laissez-faire leadership. 58 Notably, the positive influence of Transformational leadership may vary in high-challenge contexts, 21 and Ethical leadership is intricately associated with work engagement through mediation and moderation by work meaningfulness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 According to the theory of servant leadership behaviour, supervisors should base their decisions on nurses’ needs and provide them with priority services and support to enhance their sense of belonging, considering that servant leadership style positively influences nurses' engagement in work. 33 Similarly, Smith and Plunkett 34 showed that a working environment where nurses were punished for ‘mistakes’ was not conducive to building a harmonious teamwork atmosphere. Furthermore, some participants described that female nurses might need more humanistic care than male nurses, perhaps due to their lower psychological resilience, self-regulation ability and ability to withstand pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leaders should empower their nursing workforce to participate in the decision‐making processes and foster a culture of trust and independence. The positive impact of these empowering initiatives by head nurses has been found to positively influence the levels of work engagement resulting in better in‐role performance (Qin et al., 2023) and reduction of negative emotions and burnout to realize the level of servant leadership behaviours (Membrive‐Jiménez et al., 2022). In line with other researchers, we therefore, recommend training nurse leaders in the crucial skills for a servant leader to be empathetic and emotionally intelligent for better managing the well‐being of their followers (see Chang, 2020; Heinen et al., 2019).…”
Section: Implications For Nursing Managementmentioning
confidence: 99%